Abstract 115: Carotid Intraluminal Thrombus Obscuring Underlying Carotid Web: Case Report - Priya Nidamanuri; Chris Miao; Mohamed Doheim; Bishow Mahat; Bharat Pillai; Marcelo Rocha; Diogo Haussen; Raul Nogueira; Alhamza Al‐Bayati (Stroke: Vascular and Interventional Neurology)
Introduction Carotid webs (CaW) have been increasingly recognized as a unique cause of recurrent ischemic strokes.1 They are defined as thin, intraluminal, shelf‐like lesions along the posterior aspect of the carotid bulb.1,2 Despite more awareness and ongoing studies into their pathogenesis, diagnosis, and management,3 they are still overlooked in clinical practice as a primary carotid ischemic etiology. Our case describes a patient with right extracranial internal carotid artery (ICA) thrombus secondary to later‐diagnosed CaW on close follow‐up imaging. Methods We report a 55‐year‐old African American man with history of hypertension, type 2 diabetes mellitus and hyperlipidemia presented with acute onset slurred speech and left facial droop (FP). His last known well was 24 hours prior to presentation, and NIHSS upon arrival was 3 (FP 2, dysarthria 1). CT angiography (CTA) of the head and neck demonstrated a nearly occlusive thrombus of the distal right M2 segment MCA as well as non‐hemodynamic stenosis of the proximal right ICA with possible underlying sidewall filling defect‐appearing lesion concerning for a posterior wall thrombus without underlying atherosclerosis at the bulb or otherwise. The patient was admitted to the neurovascular intensive care unit and started on aspirin and high‐risk heparin drip. His MRI Brain demonstrated multiple acute/subacute right MCA territory strokes, predominately in the right posterior insula, right frontal lobe, and right posterior corona radiata. His stroke workup was otherwise unrevealing, and he was discharged on apixaban 5mg BID. Results Close surveillance follow‐up imaging with CTA head and neck was planned and obtained one month later, which demonstrated resolution of the filling defect that was obscuring the currently visualized underlying right CaW pocket (Figure‐1). The prevalence of CaWs has been reported to be between 1.2% and 2.5% of patients with acute ischemic stroke. CaWs are most frequently seen in younger, female patients, and patients with these lesions are at increased risk of recurrent stroke.4,5 Determining the optimal management for these lesions remains essential, but the available data thus far have not been conclusive. Most patients are treated with antiplatelet therapy, but some elect to treat with anticoagulation due to the focal hemostasis caused by CaWs.6 However, multiple studies have suggested that medical management alone is likely not sufficient in reducing the recurrent stroke risk caused by CaWs.5,7 Neuro‐interventional procedures including carotid artery stenting have been reported as secondary prevention strategies in patients with recurrent strokes.5,7,8 Although data regarding the rate of recurrence of strokes secondary to these lesions remains unclear, the current data does suggest benefit and safety in pursuing carotid stenting to prevent recurrent strokes.5‐8 Conclusion In young patients with proximal ICA thrombosis without underlying atherosclerosis or other conventional stroke risk factors, CaW should be considered among other differentials including hypercoagulable status. Following acute medical management, short‐term surveillance imaging is essential to confirm or rule out the diagnosis. In our case, the patient’s proximal ICA thrombus resolved after short course of anticoagulation and was determined to be secondary to the obscured underlying CaW.